2018
DOI: 10.1093/biolre/ioy079
|View full text |Cite
|
Sign up to set email alerts
|

Sox17 is essential for proper formation of the marginal zone of extraembryonic endoderm adjacent to a developing mouse placental disk†

Abstract: In mouse conceptus, two yolk-sac membranes, the parietal endoderm (PE) and visceral endoderm (VE), are involved in protecting and nourishing early-somite-stage embryos prior to the establishment of placental circulation. Both PE and VE membranes are tightly anchored to the marginal edge of the developing placental disk, in which the extraembryonic endoderm (marginal zone endoderm: ME) shows the typical flat epithelial morphology intermediate between those of PE and VE in vivo. However, the molecular characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The PrE lineage is vital for normal embryonic development and is the origin of the visceral endoderm (VE) of the visceral yolk sac, the parietal endoderm (PE) of the parietal yolk sac, and the marginal zone endoderm (MZE) lining the boundary between the placenta and chorionic plate of the placental disk ( 4 ). These extraembryonic endoderm tissues play crucial roles in nourishing the embryo through nutrient provision at the maternal-fetal interface ( 5 ), especially before the establishment of placental circulation [approximately embryonic day 10.5 (E10.5) in mice], in anterior-posterior patterning of the epiblast during gastrulation ( 6 ), and in yolk sac hematopoiesis ( 7 ).…”
mentioning
confidence: 99%
“…The PrE lineage is vital for normal embryonic development and is the origin of the visceral endoderm (VE) of the visceral yolk sac, the parietal endoderm (PE) of the parietal yolk sac, and the marginal zone endoderm (MZE) lining the boundary between the placenta and chorionic plate of the placental disk ( 4 ). These extraembryonic endoderm tissues play crucial roles in nourishing the embryo through nutrient provision at the maternal-fetal interface ( 5 ), especially before the establishment of placental circulation [approximately embryonic day 10.5 (E10.5) in mice], in anterior-posterior patterning of the epiblast during gastrulation ( 6 ), and in yolk sac hematopoiesis ( 7 ).…”
mentioning
confidence: 99%
“…These remaining PrE cells still have the ability to support the SOX17-null concepti to develop to E8.5 and E9.5 (Igarashi et al, 2018). The SOX17-null concepti showed high levels of GATA6 expression in PE cells at E8.5 and E9.5 (Igarashi et al, 2018). This result indicated that the model of sequential expression of PrE lineage-specific genes is Gata6 > Sox17 (Artus et al, 2010(Artus et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The missing SOX17 signal reduces the number of PrE cells in blastocysts (Artus et al, 2013). These remaining PrE cells still have the ability to support the SOX17-null concepti to develop to E8.5 and E9.5 (Igarashi et al, 2018). The SOX17-null concepti showed high levels of GATA6 expression in PE cells at E8.5 and E9.5 (Igarashi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nine transcription factors were identified that were actually expressed in the NR placentomes that had potential to regulate at least 4 of the 22 DEGs from day 70, although none of them were expressed differently between SGA and NonSGA placentomes. Two of the transcription factors— PPARG and SOX17 —have previously identified roles in the placenta, but the rest do not [ 43 ]. PPARG is essential for placental development, has functions in adipogenesis and inflammation, and has been previously shown to be nutrient-sensitive in the sheep placenta [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%